Comparing data accuracy between structured abstracts and full-text journal articles: implications in their use for informing clinical decisions. Issue 6 (20th June 2013) - Fontelo, Paul; Gavino, Alex; Sarmiento, Raymond Francis
Abstract : Background: The abstract is the most frequently read section of a research article. The use of 'Consensus Abstracts', a clinician-oriented web application formatted for mobile devices to search MEDLINE/PubMed, for informing clinical decisions was proposed recently; however, inaccuracies between abstracts and the full-text article have been shown. Efforts have been made to improve quality. Methods: We compared data in 60 recent-structured abstracts and full-text articles from six highly read medical journals. Results: Data inaccuracies were identified and then classified as either clinically significant or not significant. Data inaccuracies were observed in 53.33% of articles ranging from 3.33% to 45% based on the IMRAD format sections. The Results section showed the highest discrepancies (45%) although these were deemed to be mostly not significant clinically except in one. The two most common discrepancies were mismatched numbers or percentages (11.67%) and numerical data or calculations found in structured abstracts but not mentioned in the full text (40%). There was no significant relationship between journals and the presence of discrepancies (Fisher's exact p value =0.3405). Although we found a high percentage of inaccuracy between structured abstracts and full-text articles, these were not significant clinically. Conclusions: The inaccuracies do not seem to affect the conclusion and interpretation overall. Structured abstracts appear to be informative and may be useful to practitioners as a resource for guiding clinical decisions.